The Ecological Footprint of Individual Members at the Army Support Base, Eastern Cape - Fouche, Desire; Smit, Hennie; Henrico, Ivan (Scientia Militaria - South African Journal of Military Studies, 2023)
The Ecological Footprint (EF) is a measure that calculates the demand for resources from the environment based on people's needs and desires in their daily lives. This study used the Global Footprint Network (GFN) online calculator to measure the EF of Army Support Base Eastern Cape (ASB EC). The EF online survey method, a questionnaire, was used to obtain the quantitative data from the online results of each participant. Statistical analysis was performed using the STATISTICA 14.0 program to calculate the EFs of the individual ASB EC members and their combined EFs. Officers recorded the highest EFs in most categories, with non-commissioned officers (NCOs), Private Services Act (PSAP) personnel and privates in general recording the lowest scores. Males performed better than females in almost all categories, suggesting that they have a higher EF than females. The results of this study are significant as it is the first EF calculation performed for a military base in South Africa and one of only a few global studies similarly targeting the military. These results can be used as a basis for further studies in units of the SANDF, ultimately leading to more sustainable resource use.